The Social Responsibility of the Cameroonian Researcher in Management Sciences - Eustache, Essono Bella; Edouard Guilaire, Dadem Kemgou; Tobie Nicaise, Ongono Amogo; Gaelle Clarisse, Belibi Gatte (European Scientific Journal, ESJ, 2024)
This article aims to initiate a reflection on managerial CSR in the Cameroonian context. A concept still little known in Africa in general, CSR draws its sources from numerous works on CSR. A look at the state of research in Cameroon shows that the practice of responsible research is a real feat. An assessment of the apprehensions that teacher-researchers have about their SR is necessary to begin work on this theme. We are calling on different stakeholders to improve SG research in Cameroon. This improvement will undoubtedly pass better through a research model such as “Grounded theory”, considered as a reference epistemological model for better production of managerial knowledge on African soil.